2017
DOI: 10.1016/j.childyouth.2017.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Comparing children's experiences of schools-based bullying across countries

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 29 publications
1
38
0
5
Order By: Relevance
“…School bullying is one of the serious issues faced by adolescents in educational settings. Existing research has revealed that bullied adolescents are at increased risk of poor physical [5][6][7] and mental health problems (such as anxiety, depression, psychiatric disorder), with immediate to long term health impacts [8][9][10]. Bullying can even lead victims to self-harm thoughts and suicidal behavior [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…School bullying is one of the serious issues faced by adolescents in educational settings. Existing research has revealed that bullied adolescents are at increased risk of poor physical [5][6][7] and mental health problems (such as anxiety, depression, psychiatric disorder), with immediate to long term health impacts [8][9][10]. Bullying can even lead victims to self-harm thoughts and suicidal behavior [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…(Knies 2011;Rees et al 2011). Currently, studies have revealed that children's perceptions of material deprivation are related with subjective well-being (Bradshaw et al 2017;Bárcena-Martín et al 2017;Main 2018), suggesting that the child-centric method is more effective than the adult-centric method in predicting subjective well-being of children.…”
Section: Introductionmentioning
confidence: 99%
“…Bullying is a phenomenon that affects individuals across the lifespan, across multiple contexts (Bradshaw et al 2017;Craig et al 2009;Due et al 2005;Monks et al 2009) and impacts at least 10-11% of school-age children throughout the world (Jimerson et al 2010;Menesini and Salmivalli 2017;Smith and Shu 2000;Smith 2014). Bullying can involve verbal or physical attacks as well as relational manipulation (e.g., social exclusion, rumor spreading) (Olweus 1993).…”
mentioning
confidence: 99%